Tuberculous pleurisy in breast cancer patients: three clinical cases - N. A. Stogova (Туберкулез и болезни лёгких, 2018)
The objective of the study: to detect specific clinical signs of tuberculous exudative pleurisy and define the tactics for doctors from general medical services for its detection in cancer patients.Subjects and methods. The case histories of 3 patients suffering from tuberculous pleurisy at the age of 57, 58 and 59 years were analyzed; all the patients were examined and treated in Voronezh Regional TB Dispensary in 2000-2012; and earlier (8 months, 2 and 10 years before that respectively) they received combination therapy due to breast cancer.Results: The specific clinical manifestations of tuberculous pleurisy in the patients who had cancer were the absence of acute courses of the disease and no intense clinical manifestations as well as suppressed sensitivity to tuberculin. Development of pleurisy when there are no changes in the lungs and no mycobacteria are detected in sputum and pleural effusions results in difficulties in diagnostics aimed to define the etiology of pleural effusions. It was found out that the early use of puncture biopsy of parietal pleura allowed diagnosing tuberculosis within a short period of time (5-8 days).